Reinventing Pesantren Economies: Islamic Social Entrepreneurship as a Model for Sustainable Community Transformation - Zaid Raya Argantara; Slamet Haryono; Moh. Wardi; Holilur Rahman; Iqbal Rafiqi; Noor Aimi Mohamad Puad (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This study examines the role of Islamic social entrepreneurship in reinventing pesantren-based economies as a sustainable model for community transformation within the broader discourse of inclusive and ethical development. Employing a qualitative descriptive-analytical approach, data were collected through in-depth interviews, participant observation, and documentation at Pondok Pesantren Al-Amien Prenduan, Indonesia. The findings demonstrate that the implementation of Islamic social entrepreneurship through the Micro Waqf Bank (BWM) Al-Pend Barokah Mandiri significantly contributes to economic empowerment among productive low-income communities. Beyond local impact, this pesantren-based model addresses global challenges related to financial inclusion, social inequality, and sustainable development by embedding Islamic ethical values within entrepreneurial practices. The study contributes to the literature by conceptualizing pesantren not merely as religious institutions but as transformative socio-economic actors capable of driving inclusive growth. This research proposes pesantren-based Islamic social entrepreneurship as a viable alternative framework for sustainable community transformation in emerging Muslim economies.